Immunosuppressive impact of Aedes triseriatus salivary gland extract on lymphocyte biology - Ring, Molly; Valenzuela Leon, Paola Carolina; Bonilla, Brian; Wu, Jian; Percopo, Caroline; Su, Xin-zhuan; Calvo, Eric (Frontiers in Immunology, 2026)
BackgroundMosquito salivary proteins play a crucial role in blood meal acquisition and are known to disrupt host immune responses and homeostasis. Previous studies have identified salivary gland extract from the prominent arbovirus vector, Aedes aegypti, that contains pharmacologically active proteins which can induce cell death in splenic lymphocyte populations in mice. However, it has remained unclear until now whether this effect is unique to A. aegypti or conserved across other Aedes species.MethodsHere, we characterize the immunomodulatory properties of the salivary gland extracts from Aedes triseriatus, the primary vector of La Crosse virus (LACV). Murine, guinea pig, and human lymphocytes were exposed to salivary gland extracts at varying concentrations and time points. Lymphocyte proliferation was evaluated using colorimetric metabolic assays and flow cytometry analysis to characterize apoptotic mechanisms and define affected lymphocyte subsets.ResultsWe found that Ae. triseriatus salivary gland extract inhibited splenocyte proliferation in both mice and guinea pigs through the induction of apoptosis and suppression of cytokine expression. We identified a strong dose-dependent apoptotic phenotype present in CD4+, CD8+, and CD19+ lymphocytes. However, primary human lymphocytes and human lymphoid cell lines did not exhibit reduced proliferation after exposure to salivary gland extracts.ConclusionTogether, these discoveries suggest that Aedes species saliva contains evolutionarily adapted immunomodulatory proteins that could help facilitate arboviral persistence in rodent reservoirs.